ApoLänk decreases patient medication discrepancies at discharge: initial experience from a Swedish bedside pharmacy service. Issue 1 (17th July 2012) - Eriksson, Tommy; Wallin, Frida Strobel; Henricson, Karin; Lundin, Anna; Petersson, Jesper
Abstract : Objective: To develop a working model so that dispensing pharmacists, patients and medical staff can work together to identify, solve and prevent problems associated with discharge prescriptions. Methods: A routine was developed for communication between pharmacists, patients and medical staff and for dispensing drugs at the bedside. Hospital medication lists and prescriptions from the pharmacy and healthcare databases were simultaneously assessed. The study was carried out in two neurological wards in a Swedish university hospital. Results: Major shortcomings were identified in the coordination of pharmacy and healthcare records and in patients' ability to take responsibility for their medication at discharge. Discussion between patients and staff allowed discrepancies in communication and documentation to be corrected. Cooperation between pharmacists and nurses was perceived as being very positive and important. Conclusions: The Apolänk service was appreciated by nurses, is almost cost neutral and reduces discrepancies that have the potential to cause patient harm.